Analysis of the Potential and Performance of the Tourism Sector towards the Community (Study on Pasir Kencana Beach Tourism Area in Pekalongan City) - Elsa Syakira (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2024)
Purpose: Tourism has become a major growth engine in Indonesia and has helped the local economy and government. One of Indonesia's emerging economic sectors is tourism. Pekalongan is one of the most central cities in Java and has many natural and man-made tourist spots. To increase the attractiveness and sustain tourism, Pasir Kencana tourism in Pekalongan city should be properly managed. The objective of this investigation is to determine the extent to which community-based tourism (CBT) is being used, how it is implemented, and what obstacles are encountered in implementing CBT in tourism. Method: Data were collected through observations, interviews, and documentation. Data analysis was conducted through the use of the descriptive narrative method. Result: These results show that although the community has participated in tourism management, it has not reached the desired level. Pasir Kencana Beach is a good example of community-based tourism, evidenced by the activities of a good tourism outreach group (Pokdarwis). Constraints of community-based tourism management development strategies include promoting tourism, adding qualified human resources based on the field of education, using information technology to introduce and promote tourism to a wider audience; it is also possible to attract investors to help improve tourism-related infrastructure and develop tourism destinations by making the best use of available space and leveraging local uniqueness and culture to generate more revenue from visitors. Contribution: This research contributes to developing scientific concepts about community participation in developing tourist destinations.